(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the accuracy of Obstetrical Doppler ultrasound as a diagnostic modality in detection of patients with morbidly adherent placenta (MAP) and keeping per operative diagnosis as gold standard. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the department of Radiology Nishtar Hospital Multan from March 2020 to March 2021 in one-year duration. Materials and Methods: A total of one hundred and eighty patients were enrolled in study. Positive predictive value, negative predictive value, sensitivity, specificity and diagnostic accuracy were main variables of study. SPSS version 23 was used for data analysis. Tests of significance were applied and p value ≤0.05 was taken as significant. Results: The estimated sensitivity was 87.0%. The estimated specificity was 85.1%. Positive predictive value was 66.7% and negative predictive value was 95.0%. The overall diagnostic accuracy was found as 40.6%. Conclusion: Diagnostic accuracy of transabdominal Color Doppler ultrasound is much higher in detection of morbidly adherent placenta. It is safe, useful and easily available imaging technique for diagnosis of potentially harmful and life threatening obstetrical conditions.